Addition or removal of concomitant methotrexate alters adalimumab effectiveness in rheumatoid arthritis but not psoriatic arthritis. (3rd September 2019) - Behrens, F; Koehm, M; Schwaneck, EC; Schmalzing, M; Wittig, BM; Gnann, H; Greger, G; Tony, H-P; Burkhardt, H
Abstract : Objective : Randomized trials have shown that concomitant methotrexate (MTX) augments the effectiveness of tumour necrosis factor (TNF) inhibitors in rheumatoid arthritis (RA), but its benefit in psoriatic arthritis (PsA) has not been demonstrated. The goal of this study was to examine whether the impact of concomitant MTX on therapeutic outcomes in patients with PsA was similar to its effects in RA. Methods : We used data from highly comparable and concurrent observational studies of patients with PsA (N = 1424) or RA (N = 3148) who initiated adalimumab therapy during routine clinical care. The 28-joint Disease Activity Score (DAS28) and patient-reported pain scores were evaluated in patients who received 24 months of continuous treatment with adalimumab monotherapy or adalimumab + MTX and in patients who initiated or stopped concomitant MTX during ongoing adalimumab therapy. Results : Twenty-four months of continuous treatment with adalimumab + MTX was superior to adalimumab monotherapy in RA patients, while no significant difference was observed in patients with PsA. RA patients who added MTX during the study showed significant individual improvements in DAS28 and pain scores at 6 months after the change in therapy, while those who removed MTX had slight increases in disease activity. In contrast, in patients with PsA, neither initiation nor removal of MTX during continuous adalimumab therapy had a significant effect on therapeutic outcomes. Conclusion : Addition of MTX to adalimumab confers further therapeutic benefit in patients with RA, but not in those with PsA, suggesting differences in MTX effects in these two patient populations. Clinicaltrials.gov NCT01078090, NCT01077258, NCT01111240